1996
DOI: 10.1093/infdis/173.6.1304
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Cytomegalovirus DNA and Characterization of Viral Gene Expression in Bronchoalveolar Cells of Infected Patients with and without Pneumonitis

Abstract: Cytomegalovirus (CMV) is often present in bronchoalveolar lavage (BAL) fluid of immunosuppressed patients without CMV pneumonitis. The amount of viral DNA within BAL cells of patients with definite CMV pneumonitis and of viral shedders was quantitated by polymerase chain reaction (PCR) and the extent of CMV gene expression within BAL cells was defined by reverse transcription - PCR. No viral DNA was detected in 6 viral shedders, and 12 had low copy numbers (mean, 72 copies/10(5) BAL cells; median, 20) compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
2
27
0
2
Order By: Relevance
“…The findings presented herein, obtained by use of PBL samples, are similar to our previous results obtained by use [31]. Levels of CMV pp150 transcripts in blood, as measured with a semi-quantitative RT-PCR assay, also correlated positively with the viral DNA load in leukocytes ( figure 2).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings presented herein, obtained by use of PBL samples, are similar to our previous results obtained by use [31]. Levels of CMV pp150 transcripts in blood, as measured with a semi-quantitative RT-PCR assay, also correlated positively with the viral DNA load in leukocytes ( figure 2).…”
Section: Discussionsupporting
confidence: 89%
“…Levels of CMV pp150 transcripts in samples were reported as 0.5ϩ, 1ϩ, 2ϩ, 3ϩ, 4ϩ, and 5ϩ when the ratio IOD sample/IOD standard was between 0 and 0.001, 0.001 and 0.005, 0.005 and 0.01, 0.01 and 0.05, 0.05 and 0.1, and 0.1 and 0.25, respectively. To verify that the RT-PCR procedure was working correctly, we amplified cellular b-actin RNA from all RT-PCR-negative samples using the primers described by Delfau et al [26] and a protocol reported by us elsewhere [31]. This allows for distinction between DNA and RNA because of the presence of an intron within the b-actin gene.…”
Section: Methodsmentioning
confidence: 99%
“…Promising results have been also obtained by the detection of viral nucleic acid in peripheral leukocytes and in plasma [Zipeto et al, 1995]; thus, PCR is considered the most sensitive method, but only when adopted in quantitative systems, when the best results in specificity and predictive value for HCMV disease are obtained [Kuhn et al, 1994;Boivin et al, 1997]. PCR has been suggested for reproducibility in different quantitative or semiquantitative methods for the diagnosis of HCMV infection [Kagle et al, 1992;Boivin et al, 1996]. To date, the use of the different strategies seems to require standardization of all steps to be carried out, including sample processing, DNA amplification and amplicon detection [Roberts et al, 1997;Boeckh and Boivin, 1998;Haberhausen et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…There have also been investigations to determine whether the degree of viral load is correlated with respiratory disease (141,146). In a study of 27 lung transplant recipients, CMV loads of Ͼ500,000 copies/ml of BAL fluid were highly correlated with biopsy-proven CMV pneumonitis (141).…”
Section: Nucleic Acid-based Methodsmentioning
confidence: 99%